HUBUNGAN PENGETAHUAN IBU DENGAN SIKAP IBU TENTANG MASASE BAYI YANG MENGALAMI BERAT BADAN LAHIR RENDAH - Debi Novita Siregar; Herlinawati Manao; Endang Nurul Aini; Lensawati Mendrofa; Hanisah Sopiah Hasibuan (Elisabeth Health Jurnal, 2021)
Background: Low birth weight (LBW) is a health problem in many countries, especially in developing countries or countries with low socio-economic conditions. Massage is an effort to increase the baby's weight, including LBW. The purpose of the study was to find out how the relationship between mother's knowledge and mother's attitude about infant massage with low birth weight in Hilitobara Village, South Nias Regency in 2021. Methods: This type of research is a quantitative study using a cross-sectional approach, namely the researcher takes measurements or studies at one time to find out whether or not there is a relationship between two independent variables with a dependent on one measurement. This research was conducted in Hilitobara Village, South Nias Regency. The population in this study amounted to 30 infants with low birth weight. The sampling technique used was the total sampling technique, so the number of samples in this study amounted to 30 people. The data collection technique used a questionnaire sheet with Univariate and Bivariate data analysis techniques Results: The results of the Pearson ChiSquare test value from Asymp. Sig. (2-sided) is 0.050. There is a Relationship between Mother's Knowledge and Mother's Attitude About Baby Massage with Low Birth Weight in Hilitobara Village, South Nias Regency Conclusion: Massage is the right alternative for babies to increase baby's weight